The Influence of Viral Marketing and Lifestyle on the Purchase Decision of Online Shop "Shopee" in Mataram City - Yessi Putri Aulia; Lukitasari Diah; Ira Dianti (Business Management, 2025)
This study aims to determine the influence of viral marketing and lifestyle on consumer purchasing decisions on Shopee in Mataram City. Shopee, as one of the largest e-commerce platforms in Indonesia, utilizes viral marketing strategies through social media, influencers, and promotional programs to attract consumer interest. On the other hand, people's increasingly modern and practical lifestyles also influence online shopping preferences. This study used a quantitative approach with a purposive sampling method and obtained 72 respondents who were Shopee users in Mataram City. Data were collected through questionnaires and analyzed using multiple linear regression. The results showed that both viral marketing and lifestyle significantly influenced purchasing decisions. These findings indicate that appropriate marketing strategies and an understanding of consumer lifestyles can increase promotional effectiveness and customer loyalty on e-commerce platforms.